2018
DOI: 10.1111/jfbc.12728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chrysin omega‐3 and 6 fatty acid esters on mushroom tyrosinase activity, stability, and structure

Abstract: The estreification of chrysin with α‐Linolenic acid (complex I) and linoleic acid (complex II) poly unsaturated fatty acids resulted to design of new mushroom tyrosinase (MT) inhibitors. Thermodynamic parameters of enzymes, including the melting point (Tm) and ∆G values, were obtained from thermal and chemical denaturation curves. Complexes I and II showed a competitive inhibitory effect on MT with Ki values of 0.45 and 0.29 mM, respectively. The Tm values were calculated as 328.6, 322.4, and 318 K and the ∆G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…For ω3‐NA, Glu322, His855, and Asn286 were involved in a hydrogen bond with a length of 3.04, 2.89, and 2.86 Å and 6 residues (Asn260, His 263, Phe 264, Gly281, Val283, Pro 284) were involved in the hydrophobic interaction (Figures 7). In a previous study on chrysin‐ω3 and chrysin‐ω6 complexes, based on residues and hydrophobic interactions, the existence of alpha‐helixes around the active site was detected [18] . The presence of alpha helixes in picolinic and nicotinic complexes with ω3 is also confirmed [39] …”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…For ω3‐NA, Glu322, His855, and Asn286 were involved in a hydrogen bond with a length of 3.04, 2.89, and 2.86 Å and 6 residues (Asn260, His 263, Phe 264, Gly281, Val283, Pro 284) were involved in the hydrophobic interaction (Figures 7). In a previous study on chrysin‐ω3 and chrysin‐ω6 complexes, based on residues and hydrophobic interactions, the existence of alpha‐helixes around the active site was detected [18] . The presence of alpha helixes in picolinic and nicotinic complexes with ω3 is also confirmed [39] …”
Section: Resultsmentioning
confidence: 76%
“…Kinetic assessment of the enzyme activity in the presence of ω3‐NA and ω3‐PA induced a competitive manner of inhibition, with the inhibitory constant (Ki) of 5.2 and 5.1 mM, the order of ω3‐NA and ω3‐PA, respectively. In previous studies, complexes Chyrsin‐ω3 and Chyrsin‐ω6 showed a competitive inhibitory effect on MT with Ki values of 0.45 and 0.29 mM and the diphenols, nicotinic acid, and picolinic acid activity with K i of 2.4 and 2.93 mM, respectively [18,31] . The inhibition of tyrosinase activity might depend on the hydroxyl groups on the phenolic compounds of the flavonoids, which may form hydrogen bonds with the enzyme active site, inducing a competitive manner of inhibition, leading to lower enzymatic activity [32,33] .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The docking results revealed that HA and FA can bind to the active site of tyrosinase with the lowest binding energies of −4.2 and −6.4 kcal/mol, respectively. It must be mentioned that as a general rule, the lowest binding free energy of the enzyme–inhibitor binding was utilized as models for MD simulation (Farasat et al, 2020; Jamali et al, 2019). The 2D illustrations of tyrosinase–inhibitor complexes of MD simulation are displayed in Figure 5.…”
Section: Resultsmentioning
confidence: 99%